A novel technique to treat osteoporotic proximal humeral fractures with diaphyseal extension - Abotaleb, Ahmed Fouad (International Journal of Research in Orthopaedics, 2025)
Background: Recent reports of failure of proximal humeral locked plate (PHILOS) in treating comminnuted proximal humeral fractures (PHF) with diaphyseal extension (DE) prompted attempts to either augment or add more fixation which is challenged with the proximity to important neurovascular structures. Methods: Between February 2020 and May 2024, 29 patients with comminuted fractures of PHF-DE were treated at El-Hadra University Hospital with the addition of either a small locked dynamic compression plate (sLDCP) or a small locked reconstruction plate (sLRP) to the standard PHILOS plate, using the trans-deltoid approach. Results: The average follow-up (FU) period was about 19.5 months. The average age of the patients was approximately 62.6 years. Most of the patients (72.4%) were females. All patients healed their bones without needing additional procedures like bone grafts. The average healing time was just over six months. The mean visual analogue scoring system (VAS) was 8.2. At the end of the FU, there was no significant change in the neck shaft angle (p=0.7). At the end of the FU, the average Constant-Murley shoulder score was noted as 86.6, the mean Simple Shoulder Score was 79.3%, and the average score for the shoulder rating at the University of California Los Angeles (UCLA) was 31.1. No iatrogenic neurovascular fractures occurred during the study. Conclusions: Performing double plating on PHF-DE is safe. It does not increase the risk of shoulder impingement, harm to the blood supply of the humeral head, or nerve injuries caused by treatment.